Adverse Drug Reactions Among Hospitalised Patients With Chronic Kidney Disease In Dubai Hospital: With Reference To Bleeding Tendency Among Hospitalised Patients - Saheb Sharif Askari, Fatemeh (2014)
To meet the objective of the thesis, a one year observational prospective study was conducted at the renal unit of Dubai Hospital, the United Arab Emirates. Satu kajian secara pemerhatian telah dijalankan di unit buah pinggang Hospital Dubai, Emiriyah Arab Bersatu